Clinical Spectrum and Visual Outcomes of Strabismus: A Hospital-Based Study from Eastern Nepal - Chaudhary, Neha Priyadarshani; Aryal Kafle, Prerna; Goyal, Nancy; Ahmed Khan, Sajjad (Nepalese Journal of Ophthalmology, 2026)
Introduction: Strabismus, a condition marked by abnormal ocular alignment, is relatively common and can lead to amblyopia. Beyond visual impairment, it affects self-esteem, social interaction, and overall quality of life. Misconceptions and stigma may further exacerbate psychosocial challenges, making early evaluation and management essential.Objective: To assess the clinical profile, aetiology, and visual outcomes of patients with strabismus at Birat Medical College Teaching Hospital.Methodology: This analytical, cross-sectional, hospital-based study included all patients presenting with strabismus to the Ophthalmology Outpatient Department from 2024 July to 2025 June. Data on age of onset, duration, type of deviation, and associated factors were collected after ethical approval (prospectively). Convenience sampling method was utilised. Visual acuity was measured, followed by cycloplegic retinoscopy and anterior or posterior segment examinations. Ocular deviation was quantified using the Prism Bar Cover Test and Modified Krimsky Test, while binocular single vision and stereopsis were evaluated with the Worth Four Dot and Titmus Fly Tests. Ethical approval and informed consent were obtained beforehand. Data were analysed using Chi-square and t-tests.Result: A total of 102 patients were included: 57 (55.88%) males and 45 (44.12%) females. The most affected age group was 16–30 years (41, 40.20%). Esotropia was the predominant type (46, 45.10%), followed by exotropia (38, 37.30%). Congenital strabismus accounted in 59 (57.8%), and 34 (33.3%) had associated amblyopia. Stereopsis was preserved in 75 (73.3%) of patients. Esotropic patients had 0.49 times the odds of visual acuity worse than 6/18 compared to exotropes.Conclusion: Esotropia is the most common form of strabismus, with amblyopia present in one-third of cases. Early detection and intervention are critical for preserving vision and enhancing quality of life.